Pre-Admission Confirmation sebagai Instrumen Perlindungan Hukum Rumah Sakit dalam Skema Koordinasi Antar Penyelenggara Jaminan (KAPJ) - Mohamad Ihsan Ramdani; Diah Nurlita (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study is motivated by the increasing complexity of financing coordination between the National Health Insurance (BPJS Kesehatan) and supplementary health insurance providers under the Coordination of Benefits (KAPJ) scheme, which creates potential claim disputes and administrative risks for hospitals. Although Minister of Health Decree No. HK.01.07/MENKES/1117/2025 regulates payment allocation and membership verification mechanisms, it does not explicitly recognize pre-admission confirmation as a preventive legal protection instrument. This research aims to analyze the normative position of pre-admission confirmation within the KAPJ framework, conceptualize it as a preventive legal protection mechanism, and formulate a proportional implementation model. The study employs a normative juridical method using statutory and conceptual approaches through literature review of relevant regulations and scholarly works. The findings indicate that pre-admission confirmation possesses implicit normative legitimacy through membership verification obligations and system integration requirements, and functions as a risk allocation mechanism that clarifies payment responsibilities prior to service delivery. Its implementation enhances legal certainty, reduces fraud potential, and minimizes claim disputes, provided that access to emergency medical services remains guaranteed.